2016
DOI: 10.3389/fpls.2015.01226
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Factor Genes of Tall Fescue and Perennial Ryegrass in Response to Temperature Stress by RNA-Seq Analysis

Abstract: Heat shock factors (Hsfs) are important regulators of stress-response in plants. However, our understanding of Hsf genes and their responses to temperature stresses in two Pooideae cool-season grasses, Festuca arundinacea, and Lolium perenne, is limited. Here we conducted comparative transcriptome analyses of plant leaves exposed to heat or cold stress for 10 h. Approximately, 30% and 25% of the genes expressed in the two species showed significant changes under heat and cold stress, respectively, including su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 65 publications
(101 reference statements)
5
41
0
Order By: Relevance
“…Thus, the gene was named LpCYP72A161, a gene belonging to the subfamily CYP72A. Taking together results from our present and previous studies (Wang et al, 2015b), LpCYP72A161 showed a significant up-regulation upon both heat and cold stresses, suggesting that it may play a potential role in temperature stress response. While genetic sequences of CYP72A161 have been identified, the gene's function has not been studied.…”
Section: The Presumed Gene Lpcyp72a161 From Perennial Ryegrasssupporting
confidence: 58%
See 3 more Smart Citations
“…Thus, the gene was named LpCYP72A161, a gene belonging to the subfamily CYP72A. Taking together results from our present and previous studies (Wang et al, 2015b), LpCYP72A161 showed a significant up-regulation upon both heat and cold stresses, suggesting that it may play a potential role in temperature stress response. While genetic sequences of CYP72A161 have been identified, the gene's function has not been studied.…”
Section: The Presumed Gene Lpcyp72a161 From Perennial Ryegrasssupporting
confidence: 58%
“…In our previously published work (Wang et al, 2015b), we noted a high number of differentially expressed P450 s under heat and cold stress, suggesting that P450 s play an important role in the perennial ryegrass's adaption to temperature stress. Of the P450 genes, six were divided to CYP72A subfamily according to the amino acid sequence homology (Table S2).…”
Section: Identifying Lpcyp72a161 As a Gene That Responds To Temperatumentioning
confidence: 66%
See 2 more Smart Citations
“…Of course, the gene expression of psbA, psbB , and psbC is not enough. Wang et al ( 2015 ) have researched that Hsfs and their target genes in F. arundinacea and L. perenne also provied a foundation for future gene function studies to improve stress tolerance in grasses and other crops. Yang et al ( 2015 ) also have reported that TIP41 combined with TUB and ACT was stably expressed in heat-stressed leaves and these suitable reference genes in tall fescue would allow for more accurate identification of stress-tolerance genes in this stress-tolerant species.…”
Section: Discussionmentioning
confidence: 99%